2005
DOI: 10.1111/j.1365-2621.2005.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

The derivation of the GAB adsorption equation from the BDDT adsorption theory

Abstract: The BET-like adsorption equation, popularly known as the GAB equation, was derived from the BDDT adsorption equation without changes to the bulk liquid properties of multilayer molecules. Without these changes the third parameter K in the GAB equation cannot be said to measure changes in the bulk liquid properties of the multilayer molecules. Instead K measures the range of application of the GAB equation and differentiates multilayer adsorption, when K > 0.5, from singular layer adsorption, when K £ 0.5. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…Erbas¸et al (2005) reported m o values for semolina (11.8-6.45 g H 2 O per 100 g dm) and farina (9.16-6.01 g H 2 O per 100 g dm) at 20 and 35°C. The parameter k in the GAB equation is used to modify the topmost layer to put an end to the further development of bulk liquid multilayer molecules and to limit adsorption to a finite value (Caurie, 2006). It is noted that both models provide a good fit to the experimental data.…”
Section: Moisture Sorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erbas¸et al (2005) reported m o values for semolina (11.8-6.45 g H 2 O per 100 g dm) and farina (9.16-6.01 g H 2 O per 100 g dm) at 20 and 35°C. The parameter k in the GAB equation is used to modify the topmost layer to put an end to the further development of bulk liquid multilayer molecules and to limit adsorption to a finite value (Caurie, 2006). It is noted that both models provide a good fit to the experimental data.…”
Section: Moisture Sorptionmentioning
confidence: 99%
“…Table 2 shows the parameters obtained from the Caurie model, the values of the a w limits and the %RMS. On the other hand, the size of k does not only indicate the range of application of the GAB equation, but it also identifies unimolecular (k £ 0.5) from multimolecular (k > 0.5) adsorption (Caurie, 2006). However, there are differences in the parameters that are owing to the different nature of both models.…”
Section: Moisture Sorptionmentioning
confidence: 99%
“…The gradient of spreading pressure was related to the moisture gradient using the GAB isotherm. The derivation of the GAB adsorption equation from the BDDT adsorption theory was showed by the Curie [9]. In general, the BET like adsorption equation without changes to the bulk liquid properties of multilayer molecules.…”
Section: Introductuionmentioning
confidence: 99%
“…The K parameter serves as a constant that corrects the features of molecules localized in the adsorptive multi-layer in relation to the liquid phase. The magnitude of the K parameter not only indicates the range of application of the GAB equation, but also describes monomolecular (K≤0.5) and multi-layer (K>0.5) adsorption (Caurie, 2006). Chirife and Iglesias (1992) reported that the value of the K parameter depended on the type of the described product.…”
Section: Introductionmentioning
confidence: 99%